Costs of pharmacological and non-pharmacological interventions in interstitial lung disease management in Germany - Maqhuzu, Phillen Nozibuyiso; Schwarzkopf, Larissa; Markart, Philipp; Behr, Juergen; Holle, Rolf; Leidl, Reiner; Kreuter, Michael (Respiration, 2022)
Interstitial lung diseases (ILDs) are associated with a high economic burden, yet prospective data of the German healthcare system are sparse. We assessed average ILD-related costs of pharmacological and non-pharmacological (hospitalizations, outpatient, rehabilitation, physiotherapy, and medical aids) interventions in ILD.
Gesehen am 09.11.2023